Desinformación, libertad de expresión y democracia - Estefanía Jerónimo Sánchez-Beato (Universidad Hemisferios, 2022)
Freedom of expression is a fundamental right consubstantial to a democratic State. In addition to being an essential facet of human dignity, it also constitutes a basic institutional support for any political-legal system. And it is that only through the free dissemination of information and opinion can a public opinion be formed about the problems that afflict our society and the way in which the public authorities act. The first problem that this paper deals with is that new technologies have led to a flood of communications, frequently lacking in rigor of information, giving rise to the so-called disinformation. Although not a new phenomenon, it must be acknowledged that its incredibly increase through the possibilities of diffusion offered by the new channels of communication. The public authorities, and the communication supports themselves, are taking oversight measures with a view to restrict these messages. And this brings up the second question that we deal with in this paper: the restriction of freedom of expression used as an excuse to reduce the damaging effects that disinformation might produce. We will try to reflect on how to reconcile freedom of expression with the limitations and control mechanisms of this fundamental right to fight against dissemination of untruthfulness.